Archiwum kościelne. Rola i znaczenie jako miejsca przechowywania dokumentów przeszłości - Prejs, Roland (Archiwa, Biblioteki i Muzea Kościelne, 2012)
The article first presents the basic archival terminology, in particular “fond” and briefly explains characteristic features of chancery practices such as a self-contained document, a book of inscriptions, case files. The Church always paid a great attention to collecting and storing official documents created in connection with the implementation of evangelization and salvatory mission in the world. The collection of these documents grew bigger and larger as the literary culture became more common and the habit of documenting every activity in writing spread, which on a large scale occurred only in the Middle Ages. This is how the church archives were created, initially as repositories of documents. Archives in the modern sense, that is, academic institutions which collect documents relevant to understanding and study of the past appeared in the Polish land only at the end of the 18th century. Most of the Polish dioceses organized their archives in the interwar period and monasteries only after the Second World War. The Centre (Institute since 2006) for the Church Archives Libraries and Museums (established in 1956) together with the coorganizer of the Centre, the Rev. prof. dr hab. Stanisław Librowski, played an important role in the development of church archives in Poland.